2008
DOI: 10.1128/jcm.01519-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reverse Hybridization, Microarray, and Sequence Analysis for Genotyping Hepatitis B Virus

Abstract: Hepatitis B virus (HBV) genotyping has become important in epidemiological and clinical diagnoses,given the relationship between the viral genotype and the progression of disease or the appearance of antiviral resistance. Since genotyping by sequence and phylogenetic analyses is not convenient in the clinical setting, we evaluated InnoLipa HBV genotyping (Innogenetics, Belgium) and an HBV DNA-Chip (bioMerieux, France) prototype assay and compared their sequencing of the gold standard S gene, using a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…It is an improved version of an assay that was described previously (24,34) and was designed to improve nucleotide identification and to detect an extended list of mutants and the recently identified H genotype.…”
mentioning
confidence: 99%
“…It is an improved version of an assay that was described previously (24,34) and was designed to improve nucleotide identification and to detect an extended list of mutants and the recently identified H genotype.…”
mentioning
confidence: 99%
“…These findings are consistent with those of other studies that have reported that the INNO-LiPA DR assay is more sensitive than sequencing for the detection of nucleotide variations, allowing the detection of mixtures of wild-type isolates and ETV-resistant mutants (3,7). Along these lines, a recent study by Pas et al demonstrated the practicability and usefulness of HBV genotyping by the INNOLiPA DR assay and reported that they achieved a higher sensitivity and a higher specificity with this technique than with sequencing and DNA chip technologies (8). However, one disadvantage of the INNO-LiPA DR assay is the limited scope of mutations represented in the assay, based on current knowledge of ETV resistance-associated mutations.…”
mentioning
confidence: 90%
“…Microarrays have also been used to characterize and type other gastroenteritis-causing viral pathogens including rotavirus, norovirus, and astrovirus (Chizhikov et al, 2002;Honma et al, 2007;Jaaskelainen and Maunula, 2006;Lovmar et al, 2003). Beyond diarrheal illnesses, Pas et al (2008) reported the comparison of reverse hybridization, microarray, and sequence analysis for hepatitis B virus (HBV) genotyping, suggesting that the InnoLipa HBV genotyping strip assay, a microarray-based system, detected dual infections and was an easy and quick tool for HBV genotyping.…”
Section: Comparative Genomics and Microbial Typingmentioning
confidence: 99%